Surprises and insights from long-term aquatic data sets and experiments - Dodds, Walter K.; Robinson, Christopher T.; Gaiser, Evelyn E.; Hansen, Gretchen J. A.; Powell, Heather; Smith, Joseph M.; Morse, Nathaniel B.; Johnson, Sherri L.; Gregory, Stanley V.; Bell, Tisza; Kratz, Timothy K.; McDowell, William H. (My University, 2012)
Long-term research on freshwater ecosystems provides insights that can be difficult to obtain from other approaches. Widespread monitoring of ecologically relevant water-quality parameters spanning decades can facilitate important tests of ecological principles. Unique long-term data sets and analytical tools are increasingly available, allowing for powerful and synthetic analyses across sites. Long-term measurements or experiments in aquatic systems can catch rare events, changes in highly variable systems, time-lagged responses, cumulative effects of stressors, and biotic responses that encompass multiple generations. Data are available from formal networks, local to international agencies, private organizations, various institutions, and paleontological and historic records; brief literature surveys suggest much existing data are not synthesized. Ecological sciences will benefit from careful maintenance and analyses of existing long-term programs, and subsequent insights can aid in the design of effective future long-term experimental and observational efforts. Long-term research on freshwaters is particularly important because of their value to humanity.
Keywords: Data; Lakes; Streams; Freshwater; Long term